Increasing Public Cognitive Knowledge About Chronic Kidney Disease As An Effort To Improve Compliance In Medicine Through Health Education: Peningkatan Pengetahuan Kognitif Masyarakat Mengenai Gagal Ginjal Kronik Sebagai Upaya Meningkatkan Kepatuhan Dalam Pengobatan Melalui Edukasi Kesehatan (JURNAL UNEJ, 2023)
The problem of knowledge about chronic kidney disease in remote rural areas is currently still low. Low level of knowledge results in maladaptive behavior changes. Maladaptive behavior patterns such as non-compliance with chronic kidney disease treatment in patients undergoing hemodialysis. The purpose of the community service activity is to increase people's cognitive knowledge about chronic kidney disease as an effort to increase adherence in treatment through health education. The service method with Health Education uses the concept of a nurse-patient therapeutic relationship with stages: the orientation phase, the work phase, and the resolution phase. The facilities for this Health education activity use posters, leaflets and a set of questionnaires. Evaluation of the success of health education using a pre-post test questionnaire. The result of the community service activity was Health Education for 53 participants. Provision of Health Education through the right concept method to the community about increasing people's cognitive knowledge about chronic disease failure as an effort to increase adherence in treatment through education is very effective and efficient. The concept of the stages of orientation, work, termination is a method that aims to help solve public health problems in increasing knowledge.